2015
DOI: 10.1371/journal.pone.0125707
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Trait Resilience, Virtues, Post-traumatic Stress Disorder, and Post-traumatic Growth

Abstract: The present study aims to examine the relationship between trait resilience and virtues in the context of trauma. A total of 537 participants who attended the preliminary investigation and completed the Life Events Checklist were screened. Of these participants, 142 suffered from personal traumatic experiences in the past year; these individuals were qualified and invited to respond to online questionnaires to assess trait resilience, virtues (i.e., Conscientiousness, Vitality, and Relationship), post-traumati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 45 publications
9
51
2
3
Order By: Relevance
“…The pattern of associations between PTSD and resilience appears similar across research studies regardless of how resilience is conceptualized and measured. In cross‐sectional studies from a wide variety of countries, resilience has consistently been inversely correlated with PTSD (Duan, Guo & Gan, 2015; Teche et al, 2017; Zang et al, 2017), and it has often been found to moderate or mediate the impact of stress, abuse, neglect or trauma on PTSD severity (Kim, Kim, & Kong, 2017; Lee et al, 2016; Ying, Wu, Lin, & Jiang, 2014). In a longitudinal study of military service personnel, patients with low resilience were at significantly greater odds for developing PTSD, to the degree that the researchers estimated that increasing resilience by 20% could reduce the odds of developing PTSD by 73% and the incidence of PTSD by 32%, with a potential cost savings of 196 million dollars annually (Vyas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of associations between PTSD and resilience appears similar across research studies regardless of how resilience is conceptualized and measured. In cross‐sectional studies from a wide variety of countries, resilience has consistently been inversely correlated with PTSD (Duan, Guo & Gan, 2015; Teche et al, 2017; Zang et al, 2017), and it has often been found to moderate or mediate the impact of stress, abuse, neglect or trauma on PTSD severity (Kim, Kim, & Kong, 2017; Lee et al, 2016; Ying, Wu, Lin, & Jiang, 2014). In a longitudinal study of military service personnel, patients with low resilience were at significantly greater odds for developing PTSD, to the degree that the researchers estimated that increasing resilience by 20% could reduce the odds of developing PTSD by 73% and the incidence of PTSD by 32%, with a potential cost savings of 196 million dollars annually (Vyas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, this case is not constant. Studies have also indicated that people with a few positive qualities can live through traumatic events, manage them well, and stay healthy (Carver and Antoni, 2004; Duan and Guo, 2015; Duan et al, 2015a). These findings are consistent with the Cognitive Transaction Model of Stress (Lazarus and Folkman, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…However, growth requires an individual to find meaning for a traumatic event [27]. Previous studies of resilience and PTG have mostly concentrated on cancer patients [28], women with infertility [29], HIV patients [30], and people who have suffered from personal traumatic experiences in the previous year [31]. There is a lack of research on OCL people.…”
Section: Introductionmentioning
confidence: 99%